Relationship Between Soccer-Specific Skills and Skill-Related Fitness in Adolescent Soccer Players - Umut Canlı; Süleyman Viran; Cem Kurt (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to examine the relationship between soccer-specific skills and skill-related fitness in adolescent football players. Thirty male soccer players (age: 15.86 ± 0.69 years; football experience 7.10 ± 1.70 years) were recruited from a soccer team. Soccer players performed both soccer-specific skill tests and skill-related fitness tests. Soccer-specific skill tests included the Loughborough soccer passing test, Yeagley soccer test, Mor–Christian general soccer ability skill test, and the skill-related fitness tests consisted of the alternate-hand wall-toss test, countermovement jump test, sport-specific core muscle strength and stability plank test, pro-agility test, 20-m sprint test, and lower-quarter Y balance test. Pearson product-moment correlation analyses revealed a moderately positive correlation among the Mor–Christian general soccer ability skill test score (dribbling), pro-agility test score (r = 0.44, p = 0.01), and 20-m sprint time (r = 0.43, p = 0.01). There were no correlations among other variables for both the soccer-specific skill tests and skill-related fitness tests. Based on the findings of the study, we conclude that dribbling drills in soccer should be supported by agility and sprint exercises to increase dribbling speed by soccer trainers and soccer players.